The impact of exercise on prevention of sarcopenia after bariatric surgery: The study protocol of the EXPOBAR randomized controlled trial - Cláudia Amaro Santos; Ana Margarida Cinza; Ânia Laranjeira; Margarida Amaro; Manuel Carvalho; Sandra Martins; Jorge Bravo; Armando Raimundo (Contemporary Clinical Trials Communications, 2023)
Introduction: Bariatric surgery is one of the treatments for severe obesity, with proven efficacy in reducing weight and diseases associated with obesity. Weight loss associated with bariatric surgery is greatly associated with a significant reduction of skeletal muscle and bone mineral mass, which leads us to induce that after bariatric surgery, patients incur an increased risk of sarcopenia. The need for prophylactic programs that prevent sarcopenia in bariatric surgery patients seems to be one of the crucial points for the long-term surgical success of bariatric and metabolic surgery. The aim of this randomized clinical trial will be to study the effects of a 16-week supervised exercise intervention program on the prevention of sarcopenia, in patients undergoing bariatric surgery. As a secondary purpose, it is also intended to characterize metabolic risk factors, physical fitness, and quality of life in post-bariatric surgery patients. Method: A total of 45 patients on the waiting list for bariatric surgery and who have subsequently perfurgery, will be include on EXPOBAR (EXercise POst BARiatric) and randomized into 2 groups, experimental and control. The intervention starts one month after surgery, for a total of 16 weeks. Parameters of body composition, metabolic risk, quality of life, physical activity, physical fitness, and sedentary behavior will be determined. For each participant, outcomes are measured at five different time points: before the surgery, before the exercise program, after the exercise program, six and twelve months after de exercise program. Results: This study will provide the effects of a physical exercise on sarcopenia, in patients after bariatric surgery. Trial registration: The trial was registered at Clinicaltrials.gov NCT03497546.